PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) DENGAN BANTUAN MEDIA ULAR TANGGA TERHADAP HASIL BELAJAR - Minggiani, Nilan; Gumilar, Gugum; Gumilar, Rendra (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2026)
The low level of students’ learning outcomes in Economics is the main focus of this study. This research aims to analyze the improvement of students’ learning outcomes before and after the treatment and to compare the improvement between students taught using the learning model of the Teams Games Tournament (TGT) type assisted by snakes and ladders media and those taught using conventional learning methods. The study was conducted at SMA Negeri 1 Ciamis using a quantitative approach with a quasi-experimental method. The population consisted of all eleventh-grade students, with class XI F 9 as the experimental group and class XI F 8 as the control group selected through nonprobability sampling. Data were collected through pre-tests and post-tests and analyzed using IBM SPSS 26.0 with paired sample t-tests and independent sample t-tests at a 5% significance level. The results showed a significance value (Sig. 2-tailed) of 0.000, indicating a significant difference in learning outcome improvement, with the experimental group achieving higher improvement than the conventional group.